Smart Lock Application for Smart Security System in Cargo Shipment - Faisal Lubis (CSRID (Computer Science Research and Its Development Journal), 2024)
Transportation services for cargo shipment is growing rapidly during the pandemic and the post pandemic of Covid-19. However, this business is not without problems. Security disturbances during the cargo shipment process are a major problem, and this often happens in Indonesia. For this reason, this research will build a smart security system using automation technology and based on the Internet of Things (IoT). The system is a Smart Lock installed on the cargo. This smart lock can be monitored remotely, such as opening or closing the lock and the condition of the cargo in the field. Only the cargo owner can open or close the cargo lock. In addition, this system is also equipped with temperature and humidity sensor to maintain the quality of the goods in the cargo. Cargo position, temperature and temperature data can be monitored via the website by the cargo owner. The results of this research will be useful for the security system and convenience of the cargo delivery process and the digitization process will be easier to do in the future.